Developing Materials for Natural and Social Science Project of Motorcycle Engineering Department to Enhance Reading Literacy - Heri Setyoko; Sarwanto; Mohammad Masykuri; Anis Nazihah Binti Mat Daud (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to: (1) develop teaching materials for the IPAS project in the motorcycle engineering department to enhance reading literacy; (2) produce feasible teaching materials for the IPAS project in the motorcycle engineering department to improve reading literacy; and (3) evaluate the effectiveness of these materials in enhancing students' reading literacy. This research follows a Research and Development approach using the ADDIE model, which consists of five phases: Analyze, Design, Develop, Implement, and Evaluate. The study was conducted in a Vocational High School in Wonogiri Regency, Central Java, during the 2024/2025 academic year, involving 216 tenth-grade students from three schools classified as having good, moderate, and low reading literacy levels. The teaching materials were validated by experts in content, media, language, and pedagogy using a validation questionnaire. Instrument trials were analyzed for validity, reliability, discrimination index, difficulty level, and question differentiation. The effectiveness of teaching materials was analyzed by t-test. Based on the research, it's concluded that the characteristics of PjBL-based IPAS teaching materials consist of opening, content, and closing sections. The feasibility of teaching materials is declared valid and feasible to use in learning, and it is effective in improving students' reading literacy skills.